Membangun Generasi Emas Tanpa Stunting: Upaya Edukasi Stunting dan Pendampingan Gizi di Masyarakat di Desa Kunden, Banyudono - Mukti Ali Syaifuddin Putra Prasetya; Muhammad Yoga Permana; Mustofa Kurniawan; Mutia Pramodha Wardani; Luki Sri Anggorowati (Pusat Riset dan Inovasi Nasional, 2025)
Stunting is a condition of growth failure in children caused by malnutrition. One sign of stunting is a child's height that is not appropriate for their age. The number of stunting cases in Indonesia is the highest compared to lower-middle-income countries, with Indonesia ranking 5th in the world for the highest number of stunting cases. Education on stunting prevention is urgently needed, especially for pregnant women and mothers with toddlers. This community service aims to increase understanding of stunting and how to prevent it among the people of Kunden Village, Banyudono District. The method we used was qualitative through educational delivery through socialization and the provision of nutritious food. Based on the data we obtained after conducting the survey, five children were identified as stunted. During the implementation phase, we participated in integrated health service post (Posyandu) activities by checking the children's weight and height. This was followed by a socialization phase and concluded with the provision of nutritious food in the form of mung bean porridge. This activity was able to have a positive impact on the participants. A significant positive impact for the participants was a change in their attitudes toward the importance of understanding the nutritional value of food and providing appropriate parenting practices to prevent their children from experiencing stunted growth, also known as stunting.